Mproving efficacy of sport selection in football. - Dulibskyy A.V (Kharkov National Pedagogical University, 2010)
The modern aspects of preparation of juvenile football players on pioneering stages of sports takeoff are considered. The brief analysis of state of a problem of training is given impellent operations from the point of view of demands of the modern pedagogical science. Innovational approaches of construction of process of training and preparation in a system of long-term sports takeoff of juvenile football players are illuminated. Questioning 323 trainers of youthful commands, 135 trainers of professional commands, 57 students and post-graduate students is conducted. It is established, that training and competitive activity of juvenile football players should be valued in continuous unity on adequate parameters and tests of efficiency.